Upskilling automotive engineering teacher competence: Learning innovation through QR Codes - Milana, Milana; Setiawan, M. Yasep; Ranuharja, Fadhli; Hidayat, Nuzul; Purwanto, Wawan (Community Empowerment, 2025)
This community service activity aims to enhance the quality and accessibility of learning materials in automotive engineering through digitalizing teaching materials based on Quick Response (QR) codes. The training covered introducing digitalization concepts, QR code creation, and their implementation in teaching materials through lectures, demonstrations, practice, and evaluation. The results of this activity indicate an increased understanding among participants regarding digital technology and its benefits in the learning process. Teacher's competence in developing technology-based teaching modules, including integrating QR codes and the potential of TTS AI-based videos, has significantly improved. The teachers demonstrated high enthusiasm for implementing the learned materials.